Negative electrode and rechargeable lithium battery including same
By adding a compound that condenses under specific conditions to the active material layer of the negative electrode to form a film, the problems of pH decrease and temperature increase in rechargeable lithium batteries during abnormal reactions are solved, thereby improving the stability and reliability of the battery.
Patent Information
- Application Number
- CN202511089315.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-08-06
- Filing Date
- 2025-08-05
- Publication Date
- 2026-02-06
AI Technical Summary
During abnormal reactions, rechargeable lithium batteries may experience a decrease in pH and an increase in temperature, leading to an increase in electrolyte temperature and acidity, which affects the stability and reliability of the battery.
Compounds such as casein, albumin, or gelatin that coagulate at pH 5.5 or lower and/or 90°C or higher are added to the negative electrode active material layer to form a film that blocks ion current, guides the battery to shut down, and improves stability and reliability.
It effectively suppresses ion flow under abnormal conditions, prevents battery overheating, improves chemical and physical stability, and does not affect normal battery performance, thus enhancing high-temperature safety.
Smart Images

Figure CN121483967A_ABST
Abstract
Description
Technical Field
[0001] One or more embodiments of this disclosure relate to a negative electrode and a rechargeable lithium battery including the negative electrode. Background Technology
[0002] Portable information devices such as cellular phones, laptops, and smartphones, and / or electric vehicles, already use rechargeable lithium batteries with high energy density and portability as power sources. Research has been actively conducted to use rechargeable lithium batteries with high energy density as power sources for hybrid and / or electric vehicles and / or as power storage sources for energy storage systems.
[0003] Rechargeable lithium-ion batteries use an electrolyte comprising lithium salts, which can be used as or act as a lithium-ion source to enable the rechargeable lithium-ion battery to operate and to promote or enhance the movement of lithium ions between the positive and negative electrodes. However, with the operation of rechargeable lithium-ion batteries, there is a problem that the temperature and / or acidity of the electrolyte may increase, thus requiring or desiring research into ensuring or providing the stability of rechargeable lithium-ion batteries. Summary of the Invention
[0004] One or more aspects of embodiments of this disclosure relate to a negative electrode capable of forming or providing a film at relatively low pH and / or relatively high temperature during aberrant reactions (e.g., undesirable side reactions) in a rechargeable lithium battery to block ion currents (or ion flows) and guide the shutdown of the rechargeable lithium battery, thereby enabling the rechargeable lithium battery to achieve or provide improved or enhanced stability (e.g., chemical stability and / or physical stability) and reliability.
[0005] Additional aspects of the embodiments will be set forth in part in the description which follows, and in part will be apparent from the description, or may be learned by practice of the disclosed embodiments.
[0006] In one or more embodiments, the negative electrode includes a negative electrode current collector and a negative electrode active material layer on the negative electrode current collector, wherein the negative electrode active material layer includes a negative electrode active material and an additive, and the additive includes a compound that condenses under conditions of pH 5.5 or lower and / or 90°C or higher.
[0007] In one or more embodiments, a rechargeable lithium battery is provided, the rechargeable lithium battery including a negative electrode, a positive electrode, and an electrolyte as described in one or more embodiments.
[0008] If, for example, a decrease in pH and / or an increase in temperature occurs due to an abnormal reaction (e.g., an undesirable side reaction) in the rechargeable lithium battery, the negative electrode according to one or more embodiments may form or provide a film to block ion current and guide the shutdown of the rechargeable lithium battery, thereby improving or enhancing the stability (e.g., chemical stability and / or physical stability) and reliability of the rechargeable lithium battery. Attached Figure Description
[0009] The accompanying drawings are included to provide a further understanding of embodiments of the subject matter of this disclosure, and are incorporated in and constitute a part of this specification. The drawings illustrate embodiments of the subject matter of this disclosure and, together with the description, serve to explain the principles of embodiments of the subject matter of this disclosure. In the drawings: Figures 1 to 4 Each of these is a schematic diagram illustrating a rechargeable lithium battery according to one or more embodiments; Figure 5 These are differential scanning calorimetry (DSC) plots of Examples 1 to 3 and Comparative Example 1; Figure 6 These are differential capacity-voltage (dQ / dV) charge / discharge plots for Examples 1 to 3 and Comparative Example 1; Figure 7 These are electrochemical impedance spectroscopy (EIS) plots for Examples 1 to 3 and Comparative Example 1; Figure 8 It is based on the scanning electron microscope (SEM) image of the positive electrode in Example 1; and Figure 9 It is based on the SEM image of the positive electrode of Comparative Example 1. Detailed Implementation
[0010] Embodiments of this disclosure will be described in more detail below, enabling those skilled in the art to readily implement them. However, the subject matter of this disclosure may be embodied in one or more suitable forms and should not be construed as limited to the embodiments set forth herein.
[0011] The terminology used herein is for describing particular embodiments only and is not intended to limit this disclosure. Unless the context clearly requires otherwise, singular expressions include plural expressions.
[0012] As used herein, unless the context clearly indicates otherwise, the singular forms “a,” “an,” and “the” are intended to include the plural forms as well. Furthermore, the use of “may” when describing embodiments of this disclosure means “one or more embodiments of this disclosure.”
[0013] In the context of this disclosure and unless otherwise defined, the term “use” and its variations may be considered synonymous with the term “utilize” and its variations, respectively.
[0014] As used herein, the term “about” or similar terms are used as terms of approximation rather than terms of degree, and are intended to account for the inherent biases of measured or calculated values that would be recognized by one of ordinary skill in the art. As used herein, “about” or “approximation” also includes the stated value and means: within an acceptable range of deviation for a particular value, taking into account the measurement in question and errors associated with the measurement of the particular quantity (e.g., limitations of the measurement system), as determined by one of ordinary skill in the art. For example, “about” may mean within one or more standard deviations, or within ±30%, ±20%, ±10%, or ±5% of the stated value.
[0015] Any numerical range described herein is intended to include all subranges with the same numerical precision contained within the described range. For example, the range “1.0 to 10.0” is intended to include all subranges between the described minimum value 1.0 and the described maximum value 10.0 (and including both the described minimum value 1.0 and the described maximum value 10.0), such as having a minimum value equal to or greater than 1.0 and a maximum value equal to or less than 10.0, such as 2.4 to 7.6. Any maximum numerical limit described herein is intended to include all lower numerical limits contained therein, and any minimum numerical limit described in this specification is intended to include all higher numerical limits contained therein. Therefore, the applicant reserves the right to amend this specification (including the claims) to expressly describe any subranges contained within the range expressly described herein.
[0016] As used herein, “combination of” means mixtures, laminates, complexes, copolymers, alloys, blends and / or reactants of the components.
[0017] It should be understood here that terms such as “comprising,” “having,” or variations thereof are intended to specify the presence of the features, quantities, steps, elements, or combinations thereof embodied, but do not preclude the possibility of the presence or addition of one or more other features, quantities, steps, elements, or combinations thereof.
[0018] In this disclosure, it will be understood that the terms “comprising,” “including,” or “having,” or their variations, specify the presence of the stated features, integers, steps, operations, elements, and / or components, but do not preclude the presence or addition of one or more other features, integers, steps, operations, elements, components, and / or groups thereof. Furthermore, the terms “consisting of,” and “substantially consisting of,” indicate the presence of the stated features, integers, steps, operations, elements, and / or components, while other features, integers, steps, operations, elements, components, and / or groups thereof are absent or substantially absent.
[0019] In the accompanying drawings, the thickness of layers, films, panels, and / or regions may be exaggerated to effectively or appropriately illustrate the technical content of this disclosure.
[0020] Throughout the specification, the same reference numerals or symbols denote the same elements.
[0021] It will be understood that if (for example, when) an element such as a layer, film, region, or substrate is referred to as being "on" another element, then it may be directly on the other element, or there may be an intervening element therein. Conversely, if (for example, when) an element is referred to as being "directly on" another element, then there is no intervening element therein.
[0022] Here, “layer” includes not only shapes that are formed or set on the entire surface when viewed from a plan view, but also shapes that are formed or set on a portion of the surface.
[0023] Unless otherwise defined in this disclosure, particle size can be the average particle size. Furthermore, particle size can refer to the average particle size (D50) that accumulates to approximately 50% of the volume in a particle size distribution. The average particle size can be measured by methods commonly available or used by those skilled in the art (e.g., by a particle size analyzer and / or by utilizing transmission electron microscopy (TEM) images and / or scanning electron microscopy (SEM) images). In one or more embodiments, the average particle size value can also be measured and obtained by utilizing dynamic light scattering (DLS) methods, performing data analysis, counting the number of particles in each particle size range, and calculating the data. Additionally, the average particle size (D50) can be measured using laser scattering. In laser scattering, the target particles are distributed in a dispersion solvent, introduced into a laser scattering particle measuring device (e.g., an MT 3000 commercially available from Microtrac Ltd.), irradiated with 28 kHz ultrasound at 60 W power, and then the average particle size (D50) is calculated in the measuring device using a 50% standard of the particle size distribution. As used herein, unless otherwise defined, average particle size refers to the diameter (D50) of particles that constitute 50% of the total volume in a particle size distribution obtained by randomly measuring the size (e.g., diameter or major axis length) of approximately 20 particles in a scanning electron microscope image. In one or more embodiments, if the particles are spherical (e.g., substantially spherical), "diameter" or "size" refers to the particle diameter, and if the particles are non-spherical (e.g., substantially non-spherical), "diameter" or "size" refers to the major axis length.
[0024] Here, "or" will not be interpreted as having an exclusive meaning; for example, "A or B" is interpreted as including A, B, and / or A+B, etc.
[0025] Here, "metal" is interpreted as including the concepts of common metals, transition metals, and metalloids (semi-metals).
[0026] Unless otherwise defined, all terms used herein (including technical and scientific terms) shall have substantially the same meaning as commonly understood by one of ordinary skill in the art to which this disclosure pertains. It will be further understood that terms (such as those defined in commonly available or commonly used dictionaries) shall be interpreted as having a meaning consistent with their meaning in the context of the relevant field, and shall not be interpreted in an idealized or overly formalized sense unless expressly defined herein.
[0027] negative electrode In one or more embodiments, the negative electrode may include a negative electrode current collector and a layer of negative electrode active material on the negative electrode current collector.
[0028] Negative electrode active material layer The negative electrode active material layer according to one or more embodiments may include a negative electrode active material and additives, wherein the additives may include compounds that condense at pH 5.5 or lower and / or 90°C or higher (e.g., at pH 5.5 or lower and / or at 90°C or higher), and may optionally include another type (or class) of negative electrode active material, and may also include binders and / or conductive (e.g., electrically conductive) materials (e.g., electronic conductors).
[0029] According to one or more embodiments, the negative electrode active material layer may have a concentration greater than or equal to about 3.6 mg / cm³. 2 The load level, for example, is approximately 3.6 mg / cm³. 2 Approximately 10 mg / cm 2 or approximately 3.6 mg / cm 2 Approximately 4.0 mg / cm³ 2 According to one or more embodiments, it may be advantageous or beneficial for the negative electrode active material layer to achieve or provide such a loading level, and a negative electrode that meets the aforementioned loading level range can suitably or appropriately achieve or provide a rechargeable lithium battery with relatively high capacity (e.g., electrical capacity) and relatively high energy density.
[0030] Here, the term "load level" refers to the weight per unit area of the electrode (mg / cm²). 2 Typically, electrodes with an active material layer formed on a current collector are manufactured by coating a slurry containing the active material onto the current collector, drying, and pressing. The loading level is designed into the process of coating the current collector with the slurry. A higher loading level results in a larger amount of slurry being coated, a thicker active material layer, and a lower electrode density. Therefore, if the loading levels on both sides of the current collector are different, the densities on both sides may differ. For example, a low-density active material layer can be pressed more times to achieve similar densities on both sides.
[0031] additive The electrolyte of a rechargeable lithium-ion battery comprises an organic solvent and a lithium salt, wherein the lithium salt is dissolved in the organic solvent and can be used as a source to supply lithium ions in the rechargeable lithium-ion battery, enabling the rechargeable lithium-ion battery to operate and facilitating or enhancing the movement of lithium ions between the positive and negative electrodes. Examples of lithium salts may include LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiAlO2, LiAlCl4, LiPO2F2, LiCl, LiI, etc., and for example, LiPF6 may be decomposed by moisture (e.g., H2O) and / or heat into LiF and PF5 as an acidic material, and may then generate POF3 as a chemically reactive material. As a result, moisture and / or heat may increase the temperature and / or acidity of the electrolyte, and the resulting one or more chemically reactive materials may cause problems such as damage to the electrode interface, dissolution of transition metals, decomposition of the solvent included in the electrolyte, etc.
[0032] If, for example, the temperature rises due to increased acidity in situations such as lithium salt decomposition, penetration of rechargeable lithium batteries, or short circuits, the additive can guide the shutdown by forming or providing a film to block ionic currents (or ion flows). The additive can initiate a film-forming reaction at temperatures of about 90°C or higher and form or provide a film at temperatures below about 180°C (the melting point of lithium metal), which can effectively or appropriately inhibit lithium desorption or permeation (or can effectively or appropriately reduce the extent or occurrence of lithium desorption or permeation). The temperature at which the additive forms or provides the film can be from about 90°C to about 180°C, for example, from about 100°C to about 180°C, from about 100°C to about 170°C, or from about 110°C to about 170°C. In one or more embodiments, the additive can initiate a film-forming reaction, for example, at pH 5.5 or lower, such as pH 1.0 to pH 5.5, pH 2.0 to pH 5.0, or pH 3.0 to pH 4.5.
[0033] Because the additives exhibit minimal (or non-chemical) reactivity with the electrolyte in the negative electrode, they do not degrade the electrolyte and, even in small amounts, can form or provide a film to improve or enhance high-temperature safety without performance degradation, while not reducing the ionic conductivity of the negative electrode. The additives may be dispersed in the negative electrode to act as a type (or kind) of dispersant within the negative electrode during normal (e.g., non-operational) and / or operation of the rechargeable lithium battery, or may not function at all, but may form or provide a film to perform or provide a shutdown function if (e.g., when) the rechargeable lithium battery is exposed to high-temperature environments.
[0034] In one or more embodiments, the additive may include compounds that coagulate at pH 5.5 or lower and / or at about 90°C or higher, such as casein, albumin, globulin, gelatin, or combinations thereof. In one or more embodiments, it is desirable for the additive to include casein. If, for example, casein is included as an additive, casein can coagulate at an acidity of pH 5.5 or lower and / or at about 90°C or higher to form or provide a coagulated film, which can cause the rechargeable lithium battery to shut down.
[0035] Based on a 100wt% total negative electrode active material layer, compounds that condense at pH 5.5 or lower and / or at about 90°C or higher can be included in amounts from about 0.1wt% to about 10wt%, for example, from about 0.2wt% to about 8.0wt%, from about 0.3wt% to about 6.0wt%, from about 0.4wt% to about 4.0wt%, or from about 0.5wt% to about 2.0wt%. If, for example, the compounds that condense at pH 5.5 or lower and / or at 90°C or higher are included within the foregoing range, the compounds can form or provide a condensation film at a set or predetermined acidity or higher to guide shut-off and simultaneously (e.g., synchronously) suppress (or reduce the degree or occurrence of an increase in resistance, e.g., electronic resistance).
[0036] The negative electrode active material layer according to one or more embodiments may include a condensation membrane guided by compounds that condense at pH 5.5 or lower and / or 90°C or higher. The condensation membrane may be a membrane formed or provided by the condensation of compounds under abnormal conditions such as temperatures rising to or above 90°C and / or the pH of the electrolyte solution dropping below 5.5 (e.g., below 5).
[0037] Negative electrode active material The negative electrode active material may include materials that can reversibly insert / deintercalate lithium ions, lithium metal, lithium metal alloys, materials capable of doping / dedoping lithium, and / or transition metal oxides.
[0038] Materials capable of reversibly inserting / deintercalating lithium ions can include, for example, crystalline carbon, amorphous (e.g., non-crystalline) carbon, or combinations thereof, as carbon-based negative electrode active materials. Crystalline carbon can be irregular (e.g., substantially irregular), sheet-like (e.g., substantially sheet-like), plate-like (e.g., substantially plate-like), spherical (e.g., substantially spherical), and / or fibrous (e.g., substantially fibrous) natural graphite and / or artificial graphite. Amorphous (e.g., non-crystalline) carbon can be soft carbon, hard carbon, mesophase pitch carbonization products, and / or calcined coke, etc.
[0039] The lithium metal alloy may include an alloy of lithium and a material selected from sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), francium (Fr), beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), silicon (Si), antimony (Sb), lead (Pb), indium (In), zinc (Zn), barium (Ba), radium (Ra), germanium (Ge), aluminum (Al), and / or tin (Sn).
[0040] The material capable of doping / dedoping lithium may be a Si-based negative electrode active material and / or a Sn-based negative electrode active material. The Si-based negative electrode active material may include silicon, a silicon-carbon composite, SiO x (where 0 < x ≤ 2; for example, SiO2), a Si-Q alloy (where Q may be an element selected from alkali metals, alkaline earth metals, group 13 elements, group 14 elements (excluding Si), group 15 elements, group 16 elements, transition metals, rare earth elements, and combinations thereof, such as Mg, Ca, Sr, Ba, Ra, scandium (Sc), yttrium (Y), titanium (Ti), zirconium (Zr), hafnium (Hf), rutherfordium (Rf), vanadium (V), niobium (Nb), tantalum (Ta), dubnium (Db), chromium (Cr), molybdenum (Mo), tungsten (W), (Sg), technetium (Tc), rhenium (Re), (Bh), iron (Fe), Pb, ruthenium (Ru), osmium (Os), hassium (Hs), rhodium (Rh), iridium (Ir), palladium (Pd), platinum (Pt), copper (Cu), silver (Ag), gold (Au), Zn, cadmium (Cd), boron (B), Al, gallium (Ga), Sn, In, thallium (Tl), Ge, phosphorus (P), arsenic (As), Sb, bismuth (Bi), sulfur (S), selenium (Se), tellurium (Te), polonium (Po), and / or combinations thereof) and / or combinations thereof. The Sn-based negative electrode active material may be Sn, SnO x (where 0 < x ≤ 2; for example, SnO2), a Sn alloy, or a combination thereof.
[0041] The silicon-carbon composite may be a composite of silicon and amorphous (e.g., non-crystalline) carbon. The average particle size (D50) of the silicon-carbon composite particles may be, for example, about 0.5 μm to about 20 μm. According to one or more embodiments, the silicon-carbon composite may be in the form of silicon particles and amorphous (e.g., non-crystalline) carbon coated on the surface of the silicon particles. For example, it may include secondary particles (cores) assembled from silicon primary particles and an amorphous (e.g., non-crystalline) carbon coating (shell) on the surface of the secondary particles. The amorphous (e.g., non-crystalline) carbon may also be between the silicon primary particles. For example, the silicon primary particles may be coated with amorphous (e.g., non-crystalline) carbon. The secondary particles may be dispersed in the amorphous (e.g., non-crystalline) carbon matrix.
[0042] The silicon-carbon composite may also include crystalline carbon. For example, the silicon-carbon composite may include a core containing crystalline carbon and silicon particles and an amorphous (e.g., non-crystalline) carbon coating on the surface of the core. The crystalline carbon may be artificial graphite, natural graphite, and / or a combination thereof. The amorphous (e.g., non-crystalline) carbon may include soft carbon, hard carbon, mesophase pitch carbonized products, and / or calcined coke.
[0043] If (e.g., when) the silicon-carbon composite includes silicon and amorphous (e.g., non-crystalline) carbon, based on 100 wt% of the silicon-carbon composite, the content (e.g., amount) of silicon may be from about 10 wt% to about 50 wt%, and the content (e.g., amount) of amorphous (e.g., non-crystalline) carbon may be from about 50 wt% to about 90 wt%. If (e.g., when) the composite includes silicon, amorphous (e.g., non-crystalline) carbon, and crystalline carbon, based on 100 wt% of the silicon-carbon composite, the content (e.g., amount) of silicon may be from about 10 wt% to about 50 wt%, the content (e.g., amount) of crystalline carbon may be from about 10 wt% to about 70 wt%, and the content (e.g., amount) of amorphous (e.g., non-crystalline) carbon may be from about 20 wt% to about 40 wt%.
[0044] The thickness of the amorphous (e.g., non-crystalline) carbon coating may be from about 5 nm to about 100 nm. The average particle size (D50) of the silicon particles (primary particles) may be from about 10 nm to about 1 μm or from about 10 nm to about 200 nm. The silicon particles may exist as individual silicon, in the form of a silicon alloy, and / or in an oxidized form. The oxidized form of silicon may be represented by SiO x (where 0 < x ≤ 2; e.g., SiO2). In one or more embodiments, the atomic content (e.g., amount) ratio of Si:O (which refers to the degree of oxidation) may be from about 99:1 to about 33:67. As used herein, if (e.g., when) no other definition is provided, the average particle size (D50) refers to the particles with a cumulative volume of about 50 volume% in the particle distribution.
[0045] Si-based negative electrode active materials and / or Sn-based negative electrode active materials may be mixed with carbon-based negative electrode active materials. If (e.g., when) the carbon-based negative electrode active material is mixed and used with the Si-based negative electrode active material or the Sn-based negative electrode active material, the mixing ratio may be a weight ratio of from about 1:99 to about 90:10.
[0046] Binder A binder may be used to make the negative electrode active material particles adhere well or properly to each other and also to make the negative electrode active material adhere to the current collector. The binder may be a non-aqueous (e.g., water-insoluble) binder, an aqueous (e.g., water-soluble) binder, a dry binder, or a combination thereof.
[0047] Non-aqueous (e.g., water-insoluble) adhesives may include polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene-propylene copolymer, polystyrene, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamide-imide, polyimide, or combinations thereof.
[0048] Waterborne (e.g., water-soluble) adhesives may include styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, (meth)acrylonitrile-butadiene rubber, (meth)acrylic rubber, butyl rubber, fluororubber, polyethylene oxide, polyvinylpyrrolidone, polyepoxychloropropane, polyphosphazene, poly(meth)acrylonitrile, ethylene propylene diene copolymer, polyvinylpyridine, chlorosulfonated polyethylene, latex, polyester resin, (meth)acrylic resin, phenolic resin, epoxy resin, polyvinyl alcohol, or combinations thereof.
[0049] If (for example, when) an aqueous (e.g., water-soluble) binder is used as a negative electrode binder, a thickener may be further included, and a cellulose compound may also be included as a thickener. As a cellulose compound, one or more of carboxymethyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose, or their alkali metal salts may be used in combination. The alkali metal may be sodium (Na), potassium (K), or lithium (Li).
[0050] The dry binder can be a polymeric material that can be turned into fibers (e.g., processed to become fibers), and can be, for example, polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide, or a combination thereof.
[0051] conductive materials Conductive (e.g., electrically conductive) materials (e.g., electronic conductors) may be included to provide electrode conductivity (e.g., electrical conductivity), and any suitable electrically conductive material may be used as a conductive material unless it causes a chemical change (e.g., an undesirable chemical change). Examples of conductive (e.g., electrically conductive) materials may include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fibers, carbon nanofibers, carbon nanotubes, etc.; metallic materials including metal powders and / or metal fibers of copper, nickel, aluminum, silver, etc.; conductive (e.g., electrically conductive) polymers such as polyphenylene and / or polyphenylene derivatives; MXene; and / or mixtures thereof.
[0052] Negative electrode current collector The negative electrode current collector may include copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, polymer substrate coated with a conductive (e.g., electrically conductive) metal, and / or combinations thereof.
[0053] Rechargeable lithium batteries In one or more embodiments, the rechargeable lithium battery may include a negative electrode, a positive electrode, and an electrolyte as described in one or more embodiments. In one or more embodiments, the electrolyte may be a liquid electrolyte and / or a solid electrolyte.
[0054] For example, in one or more embodiments, a rechargeable lithium battery may include a negative electrode, a positive electrode, a separator between the negative and positive electrodes, and an electrolyte solution as described in one or more embodiments. As another example, an all-solid-state rechargeable lithium battery may include a negative electrode, a positive electrode, and a solid electrolyte layer between the negative and positive electrodes as described in one or more embodiments.
[0055] The following text will describe a rechargeable lithium battery using an electrolyte solution as an example.
[0056] Rechargeable lithium batteries can be classified according to their shape into cylindrical, prismatic, pouch, or coin-shaped (or other types) rechargeable lithium batteries. Figures 1 to 4 Each is a schematic diagram illustrating a rechargeable lithium battery according to one or more embodiments. Figure 1 It is a cylindrical rechargeable lithium battery. Figure 2 It is a prismatic rechargeable lithium battery. Figure 3 and Figure 4 It is a pouch-shaped rechargeable lithium battery. (See reference) Figures 1 to 4 The rechargeable lithium battery 100 may include an electrode assembly 40 having a separator 30 between a positive electrode 10 and a negative electrode 20, and a housing 50 housing the electrode assembly 40. The positive electrode 10, negative electrode 20, and separator 30 may be impregnated / immersed in an electrolyte solution. Figure 1 As shown, the rechargeable lithium battery 100 may include a sealing member 60 of the sealed housing 50. Figure 2 In this context, the rechargeable lithium battery 100 may include a positive electrode lead connector 11, a positive electrode terminal 12, a negative electrode lead connector 21, and a negative electrode terminal 22. For example... Figure 3 and Figure 4 As shown, the rechargeable lithium battery 100 may include electrode terminals 70 (e.g., positive electrode terminal 71 and negative electrode terminal 72) that serve as electrical paths to guide current formed or provided in the electrode assembly 40 to the outside.
[0057] positive electrode The positive electrode may include a positive electrode current collector and a layer of positive electrode active material on the positive electrode current collector. The positive electrode active material layer may include a positive electrode active material and may also include a binder and / or a conductive (e.g., electrically conductive) material (e.g., an electronic conductor).
[0058] The positive electrode active material can be a compound capable of inserting and deintercalating lithium (lithiation intercalation compound). For example, a composite oxide of lithium with one or more types (or kinds) of metals selected from cobalt, manganese, nickel and combinations thereof can be used.
[0059] The composite oxide can be a lithium transition metal composite oxide, and one or more examples may include lithium nickel oxides, lithium cobalt oxides, lithium manganese oxides, lithium iron phosphate compounds, cobalt-free lithium nickel manganese oxides, and / or combinations thereof.
[0060] As an example, a compound represented by any of the following chemical formulas can be used: Li a A 1-b X b O 2-c D c (0.90≤a≤1.8, 0≤b≤0.5 and 0≤c≤0.05); Li a Mn 2-b X b O 4-c D c (0.90≤a≤1.8, 0≤b≤0.5 and 0≤c≤0.05); Li a Ni 1-b-c Co b X c O 2-α D α (0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.5 and 0<α<2); Li a Ni 1-b-c Mn b X c O 2-α D α (0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.5 and 0<α<2); Li a Ni b Co c L 1 d G e O2 (0.90≤a≤1.8, 0≤b≤0.9, 0≤c≤0.5, 0≤d≤0.5 and 0≤e≤0.1); Li a NiG b O2 (0.90≤a≤1.8 and 0.001≤b≤0.1); Li a CoG b O2 (0.90≤a≤1.8 and 0.001≤b≤0.1); Li a Mn 1-b G bO2 (0.90≤a≤1.8 and 0.001≤b≤0.1); Li a Mn2G b O4 (0.90≤a≤1.8 and 0.001≤b≤0.1); Li a Mn 1-g G g PO4 (0.90≤a≤1.8 and 0≤g≤0.5); Li (3-f) Fe2(PO4)3 (0≤f≤2); and Li a FePO4 (0.90≤a≤1.8).
[0061] In the aforementioned chemical formula, A can be nickel (Ni), cobalt (Co), manganese (Mn), or a combination thereof; X can be Al, Ni, Co, Mn, Cr, Fe, Mg, Sr, V, rare earth elements, or a combination thereof; D can be oxygen (O), fluorine (F), S, P, or a combination thereof; G can be Al, Cr, Mn, Fe, Mg, lanthanum (La), cerium (Ce), Sr, V, or a combination thereof; and L 1 It can be Mn, Al, or a combination thereof.
[0062] For example, the positive electrode active material can be a high-nickel positive electrode active material, wherein, based on 100 mol% of metals other than lithium in the lithium transition metal composite oxide, the nickel content (e.g., amount) of the high-nickel positive electrode active material is greater than or equal to about 80 mol%, greater than or equal to about 85 mol%, greater than or equal to about 90 mol%, greater than or equal to about 91%, or greater than or equal to about 94 mol% and less than or equal to about 99 mol%. High-nickel positive electrode active materials can achieve or provide relatively high capacity (e.g., charge capacity) and can be applied to high-capacity (e.g., charge capacity) and / or high-density rechargeable lithium batteries.
[0063] Based on the total weight of the positive electrode active material layer (e.g., based on 100 wt% of the positive electrode active material layer), the content (e.g., amount) of the positive electrode active material can be from about 90 wt% to about 98 wt%, for example, from about 90 wt% to about 95 wt%. Based on the total weight of the positive electrode active material layer (e.g., based on 100 wt% of the positive electrode active material layer), the respective content (e.g., amount) of the binder and the conductive (e.g., electrically conductive) material (e.g., electronic conductor) can be from about 1 wt% to about 5 wt%.
[0064] The binder can be used to make the positive electrode active material particles adhere well or suitably to each other, and also to make the positive electrode active material adhere well or suitably to the current collector, and examples may include polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, nylon, etc., but the embodiments of this disclosure are not limited thereto.
[0065] Conductive (e.g., electrically conductive) materials (e.g., electronic conductors) may be included to provide electrode conductivity (e.g., electrical conductivity), and any suitable electrically conductive material may be used as a conductive material unless it causes a chemical change (e.g., an undesirable chemical change). Examples of conductive (e.g., electrically conductive) materials (e.g., electronic conductors) may include: carbon-based materials, such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fibers, carbon nanotubes, etc.; metallic materials including metal powders and / or metal fibers of copper, nickel, aluminum, silver, etc.; conductive (e.g., electrically conductive) polymers, such as polyphenylene and / or polyphenylene derivatives; MXene; and / or mixtures thereof.
[0066] The positive electrode current collector can be aluminum foil, but the embodiments of this disclosure are not limited thereto.
[0067] electrolytes The electrolyte used in rechargeable lithium batteries can be, for example, an electrolyte solution, which may include a non-aqueous (e.g., water-insoluble) organic solvent and a lithium salt.
[0068] Non-aqueous (e.g., water-insoluble) organic solvents can be used as media for transporting ions that participate in the electrochemical reactions of rechargeable lithium batteries. Non-aqueous (e.g., water-insoluble) organic solvents can be carbonate solvents, ester solvents, ether solvents, ketone solvents, alcohol solvents, aprotic solvents, and / or combinations thereof.
[0069] Carbonate solvents can include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), and butyl carbonate (BC), etc. Ester solvents can include methyl acetate, ethyl acetate, n-propyl acetate, dimethyl acetate, (2-fluoroethyl) acetate, 2,2-difluoroethyl acetate, methyl propionate, ethyl propionate, propyl propionate, butyl propionate, decanolactone, mevalonolactone, valproic acid lactone, caprolactone, etc. Ether solvents can include dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, dimethoxyethane, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, tetrahydrofuran, etc. Ketone solvents can include cyclohexanone, etc. Alcohol solvents may include ethanol, isopropanol, etc., and aprotic solvents may include nitriles, such as R-CN (where R may be a C2 to C20 straight-chain, branched or cyclic hydrocarbon group and may include double bonds, aromatic rings and / or ether groups, etc.); amides, such as dimethylformamide; dioxolane, such as 1,3-dioxolane, 1,4-dioxolane, etc.; sulfolane; etc.
[0070] Non-aqueous (e.g., water-insoluble) organic solvents may be used alone or in mixtures of two or more types (or kinds), and if (e.g., when) two or more types (or kinds) are used in mixtures, the mixing ratio may be appropriately or suitably adjusted according to the desired or suitable rechargeable lithium battery performance, which is generally available to or used by those skilled in the art.
[0071] When using carbonate solvents, cyclic carbonates and chain carbonates can be mixed and used, and the cyclic carbonates and chain carbonates can be mixed in a volume ratio of about 1:1 to about 1:9.
[0072] Non-aqueous (e.g., water-insoluble) organic solvents may further include aromatic hydrocarbon organic solvents. For example, carbonate solvents and aromatic hydrocarbon organic solvents may be mixed and used in a volume ratio of about 1:1 to about 30:1.
[0073] The electrolyte solution may also include vinyl ethyl carbonate, vinylene carbonate and / or ethylene carbonate compounds to improve or enhance the cycle life of rechargeable lithium batteries.
[0074] Examples of ethylene carbonate compounds may include fluoroethylene carbonate, difluoroethylene carbonate, chloroethylene carbonate, dichloroethylene carbonate, bromoethylene carbonate, dibromoethylene carbonate, nitroethylene carbonate, and / or cyanoethylene carbonate.
[0075] Lithium salts dissolved in organic solvents can supply lithium ions in rechargeable lithium batteries, enabling basic operation and improving or enhancing lithium ion transport between the positive and negative electrodes. Examples of lithium salts may include those selected from LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiAlO2, LiAlCl4, LiPO2F2, LiCl, LiI, LiN(SO3C2F5)2, Li(FSO2)2N (lithium bis(fluorosulfonyl)imide; LiFSI), LiC4F9SO3, LiN(C x F 2x+1 SO2)(C y F 2y+ The lithium trifluoromethane sulfonate (where x and y are integers from 1 to 20), lithium tetrafluoroethane sulfonate, lithium difluorobis(oxalate)phosphate (LiDFBOP), lithium difluorobis(oxalate)borate (LiDFBOB), and / or lithium bis(oxalate)borate (LiBOB).
[0076] The concentration of lithium salt can be in the range of about 0.1 M to about 2.0 M. If (for example, when) the concentration of lithium salt is in the above range, the electrolyte solution can have appropriate or suitable ionic conductivity and viscosity, thus achieving or providing excellent or suitable performance, and lithium ions can move efficiently or appropriately.
[0077] diaphragm Depending on the type (or category) of the rechargeable lithium battery, the separator can be located between the positive and negative electrodes. The separator may include multilayer membranes of polyethylene, polypropylene, polyvinylidene fluoride and / or two or more layers thereof, as well as hybrid multilayer membranes (such as polyethylene / polypropylene double-layer membranes, polyethylene / polypropylene / polyethylene triple-layer membranes, polypropylene / polyethylene / polypropylene triple-layer membranes, etc.).
[0078] The membrane may include a porous substrate and a coating on one or both surfaces of the porous substrate (e.g., two opposite surfaces) comprising an organic material, an inorganic material, or a combination thereof.
[0079] Porous substrates can be selected from polyolefins (such as polyethylene and polypropylene), polyesters (such as polyethylene terephthalate and polybutylene terephthalate), polyacetals, polyamides, polyimides, polycarbonates, polyetherketones, polyaryletherketones, polyetherimides, polyamideimides, polybenzimidazoles, polyethersulfones, polyphenylene ethers, cyclic olefin copolymers, polyphenylene sulfide, polyethylene naphthalate, glass fiber, and polytetrafluoroethylene (Teflon). TM A polymer film of any one of the polymers of ( ) or copolymers or mixtures thereof.
[0080] The porous substrate can have a thickness of about 1 μm to about 40 μm, for example, about 1 μm to about 30 μm, about 1 μm to about 20 μm, about 5 μm to about 15 μm, or about 10 μm to about 15 μm.
[0081] Organic materials may include (meth)acrylic acid copolymers comprising a first structural unit and a second structural unit, wherein the first structural unit is derived from (meth)acrylamide and the second structural unit comprises at least one selected from structural units derived from (meth)acrylic acid and / or (meth)acrylates and structural units derived from (meth)acrylamidosulfonic acid and / or salts thereof.
[0082] Inorganic materials may include inorganic particles selected from Al2O3, SiO2, TiO2, SnO2, CeO2, MgO, NiO, CaO, GaO, ZnO, ZrO2, Y2O3, SrTiO3, BaTiO3, Mg(OH)2, boehmite, and combinations thereof, but the embodiments of this disclosure are not limited thereto. The average particle size (D50) of the inorganic particles may be from about 1 nm to about 2000 nm, for example, from about 100 nm to about 1000 nm or from about 100 nm to about 700 nm.
[0083] Organic and inorganic materials can be mixed in a coating, or coatings containing organic materials and coatings containing inorganic materials can be stacked.
[0084] The thickness of the coating can be from about 0.5 μm to about 20 μm, for example, from about 1 μm to about 10 μm or from about 1 μm to about 5 μm.
[0085] Examples and comparative examples of this disclosure are described in more detail herein. However, the following examples are merely embodiments of this disclosure, and embodiments of this disclosure are not limited to the following examples.
[0086] Example 1 A slurry for the negative electrode active material layer was prepared by mixing 94.0 wt% graphite negative electrode active material, 2.0 wt% casein, 1.5 wt% carboxymethyl cellulose, 1.5 wt% styrene-butadiene rubber, and 1.0 wt% carbon nanotube conductive (e.g., electrically conductive) material. The negative electrode active material layer slurry was coated onto a copper foil current collector, then dried and pressed to fabricate the negative electrode. Here, the formed or obtained negative electrode active material layer has a strength of 3.64 mg / cm². 2 The load level.
[0087] By using 98.5wt% LiNi 0.8 Co 0.1 Mn 0.1A slurry for preparing the positive electrode active material layer is prepared by mixing O2-based positive electrode active material, 1.0 wt% polyvinylidene fluoride binder, and 0.5 wt% carbon nanotube conductive (e.g., electrically conductive) material. This slurry is coated onto an aluminum foil current collector, then dried and pressed to fabricate the positive electrode. Here, the formed or obtained positive electrode active material layer has a concentration of 6 mg / cm³. 2 The load level.
[0088] A basic electrolyte solution was prepared using a 14 μm thick polytetrafluoroethylene (PTFE) membrane by mixing ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) in a volume ratio of 2:4:4, and then dissolving 1.15 M LiPF6 in this mixed solvent. An electrolyte solution was prepared by adding 1.5 wt% vinylene carbonate (VC) and 0.5 wt% vinyl ethylene carbonate (VEC) to a 98.0 wt% basic electrolyte solution. This electrolyte solution is used to manufacture rechargeable lithium-ion battery cells.
[0089] Example 2 The negative electrode and rechargeable lithium battery cell were manufactured in essentially the same manner as in Example 1, except that in the manufacture of the negative electrode, a loading level of 3.80 mg / cm³ was achieved by using 90.0 wt% graphite negative electrode active material and 6.0 wt% casein. 2 The negative electrode active material layer.
[0090] Example 3 The negative electrode and rechargeable lithium battery cell were manufactured in essentially the same manner as in Example 1, except that in the manufacture of the negative electrode, a loading level of 3.97 mg / cm³ was achieved by using 86.0 wt% graphite negative electrode active material and 10.0 wt% casein. 2 The negative electrode active material layer.
[0091] Example 4 The negative electrode and rechargeable lithium battery cell were manufactured in essentially the same manner as in Example 1, except that in the manufacture of the negative electrode, a loading level of 3.97 mg / cm³ was achieved by using 95.8 wt% graphite negative electrode active material and 0.2 wt% casein. 2 The negative electrode active material layer.
[0092] Example 5 The negative electrode and rechargeable lithium battery cell were manufactured in essentially the same manner as in Example 1, except that in the manufacture of the negative electrode, a loading level of 3.97 mg / cm³ was achieved by using 95.5 wt% graphite negative electrode active material and 0.5 wt% casein. 2 The negative electrode active material layer.
[0093] Comparison Example 1 The negative electrode and rechargeable lithium battery cell were manufactured in essentially the same manner as in Example 1, except that in the manufacture of the negative electrode, a loading level of 3.56 mg / cm³ was achieved by using 96.0 wt% graphite negative electrode active material instead of casein. 2 The negative electrode active material layer.
[0094] Comparison Example 2 The negative electrode and rechargeable lithium battery cell are manufactured in essentially the same manner as in Example 1, except that trypsin is used instead of casein in the manufacture of the negative electrode.
[0095] Compare Example 3 The negative electrode and rechargeable lithium battery cell are manufactured in essentially the same manner as in Example 1, except that lysozyme is used instead of casein in the manufacture of the negative electrode.
[0096] Evaluation Example 1: Evaluation of Initial Charge / Discharge Capacity and Efficiency The rechargeable lithium-ion battery cells of the example and comparative examples were charged at a constant current of 0.1C to an upper limit voltage of 4.2V, and then charged at a constant voltage to 0.02C, and then discharged at 0.1C to a cutoff voltage of 3.0V at 25°C for initial charge and discharge. Table 1 shows the initial charge capacity, initial discharge capacity, and the ratio of the latter to the former as efficiency.
[0097] Evaluation Example 2: Evaluation of Exothermic Characteristics The heat flow of the rechargeable lithium-ion battery cells of the example and comparative examples, based on temperature, was measured using differential scanning calorimetry (DSC). Measurements were performed using a differential scanning calorimeter, specifically, 15 mg of each electrode was charged to 4.2 V (vs. Li / Li). + ), added 20 μL of electrolyte solution, and heated it to 400 °C at a rate of 10 °C per minute, and the results are shown in Table 1 and Figure 5 middle.
[0098] Table 1
[0099] Refer to Table 1 and Figure 5The rechargeable lithium-ion battery cells of Examples 1 to 3 exhibit high onset temperatures and improved high-temperature cycle life characteristics due to reduced exothermicity. Conversely, the rechargeable lithium-ion battery cell of Comparative Example 1, which does not contain casein, exhibits a low onset temperature and confirms that it exhibits poorer high-temperature cycle life characteristics than those of Examples 1 to 3. In other words, it is confirmed that casein reduces exothermicity and delays the exothermic temperature due to its endothermic reaction at high temperatures, which leads to the suppression of heat accumulation within the rechargeable lithium-ion battery cell.
[0100] Evaluation Example 3: Differential Capacity Evaluation The rechargeable lithium-ion battery cells of the example and comparative examples underwent initial charging and discharging as in Evaluation Example 1, followed by three charge-discharge cycles, and their charge-discharge differential curves are shown in... Figure 6 In the differential capacity-voltage (dQ / dV) charging and discharging curve graph, the X-axis represents the voltage V, and the Y-axis represents the value obtained by differentiating the charging / discharging capacity (Q) from the voltage (V) (dQ / dV).
[0101] Reference Figure 6 The rechargeable lithium-ion battery cells of Examples 1 to 3 exhibit dQ / dV that is comparable to or higher than that of Comparative Example 1.
[0102] Evaluation Example 4: Interface Resistance Evaluation The interfacial resistance on the electrodes of the example and comparative examples of rechargeable lithium-ion battery cells was measured using electrochemical impedance spectroscopy (EIS), and the results are shown in... Figure 7 And as shown in Table 2. The amplitude is ±10mV, and the frequency is in the range of 10mHz to 1MHz. The resistance was measured by charging the battery to the maximum reference voltage of the Li negative electrode at a constant current rate of 0.1C and cutting off at a current rate of 0.05C while maintaining a constant voltage of 4.2V, and then pausing for 1 hour. Subsequently, the resistance was measured at the equilibrium voltage using an impedance analyzer according to the 2-probe method.
[0103] Table 2
[0104] Referring to Table 2, Examples 1, 2, and 5, containing 0.5 wt% or more casein, exhibited a shut-off due to a sharp increase in interfacial resistance after exposure to 120°C. However, Comparative Example 1 (excluding casein), Example 4 (containing 0.2 wt% casein), Comparative Example 2 (containing trypsin), and Comparative Example 3 (containing lysozyme) did not exhibit a shut-off even after exposure to 120°C. However, Example 2, containing 6.0 wt% casein, exhibited a relatively high interfacial resistance before exposure to 120°C.
[0105] Reference Figure 7 Compared to Comparative Example 1, the rechargeable lithium-ion battery cells of Examples 1 to 3 exhibit reduced interface resistance, and, for example, the rechargeable lithium-ion battery cell of Example 3 exhibits the lowest interface resistance. Low interface resistance (R0) ct (Charge transfer resistor) promotes the insertion / extraction of lithium ions during charging and discharging, and maintains charging / discharging efficiency, thereby significantly improving the cycle life characteristics of the battery.
[0106] Evaluation Example 5: Structural Analysis The structure of the sample and comparative examples of rechargeable lithium battery cells was examined using SEM.
[0107] Reference Figure 8 It was confirmed that the rechargeable lithium-ion battery cell in Example 1 exhibits the following property: casein coagulates under high acidity to form a coagulated film. Conversely, refer to... Figure 9 In the rechargeable lithium battery cell of Comparative Example 1, it was confirmed that no separate condensation film was formed.
[0108] While the subject matter of this disclosure has been described in conjunction with what are now considered to be practical exemplary embodiments, it will be understood that this disclosure is not limited to the disclosed embodiments. Rather, it is intended to cover one or more suitable modifications and equivalent arrangements included within the spirit and scope of the appended claims and their equivalents. Therefore, it will be understood that the foregoing one or more embodiments are illustrative in all respects and not restrictive.
[0109] Figure Labels 100: Rechargeable lithium battery 10: Positive electrode 11: Positive electrode lead connector 12: Positive electrode terminal 20: Negative electrode 21: Negative electrode lead connector 22: Negative electrode terminal 30: Diaphragm 40: Electrode assembly 50: Casing 60: Sealing component 70: Electrode connector 71: Positive electrode connector 72: Negative electrode connector.
Claims
1. A negative electrode, the negative electrode comprising: Negative electrode current collector; as well as The negative electrode active material layer is located on the negative electrode current collector. The negative electrode active material layer includes a negative electrode active material and additives, and The additive is a compound that condenses under conditions of pH 5.5 or lower or 90°C or higher.
2. The negative electrode according to claim 1, wherein: The compounds that coagulate at pH 5.5 or lower or at 90°C or higher include casein, albumin, globulin, gelatin, or combinations thereof.
3. The negative electrode according to claim 1, wherein: The compound that coagulates at pH 5.5 or lower or at 90°C or higher is casein.
4. The negative electrode according to claim 1, wherein: Based on 100 wt% of the negative electrode active material layer, the compound is included in amounts from 0.1 wt% to 10 wt% under conditions of pH 5.5 or lower or 90°C or higher.
5. The negative electrode according to claim 1, wherein: Based on 100 wt% of the negative electrode active material layer, the compound is included in an amount of 0.5 wt% to 2.0 wt% at conditions of pH 5.5 or lower or 90°C or higher.
6. The negative electrode according to claim 1, wherein: The negative electrode active material layer also includes a condensation membrane derived from the compound condensed at pH 5.5 or lower or at 90°C or higher.
7. The negative electrode according to claim 1, wherein: The negative electrode active material includes carbon-based negative electrode active materials, lithium metal, lithium metal alloys, silicon-based negative electrode active materials, or combinations thereof.
8. The negative electrode according to claim 1, wherein: The negative electrode active material layer also includes a binder.
9. The negative electrode according to claim 1, wherein: The negative electrode active material layer also includes an aqueous binder and a thickener.
10. The negative electrode according to claim 1, wherein: The active material layer of the negative electrode has a concentration greater than or equal to 3.6 mg / cm³. 2 The load level.
11. A rechargeable lithium battery, said rechargeable lithium battery comprising: The negative electrode according to any one of claims 1 to 10; Positive electrode; as well as Electrolytes.
12. The rechargeable lithium battery according to claim 11, wherein: The positive electrode includes a positive electrode current collector and a layer of positive electrode active material on the positive electrode current collector, and The positive electrode active material layer includes a positive electrode active material.
13. The rechargeable lithium battery according to claim 12, wherein: The positive electrode active material comprises a compound represented by one of the following chemical formulas: Li a A 1-b X b O 2-c D c , 0.90≤a≤1.8, 0≤b≤0.5 and 0≤c≤0.05; Li a Mn 2-b X b O 4-c D c , 0.90≤a≤1.8, 0≤b≤0.5 and 0≤c≤0.05; Li a Ni 1-b-c Co b X c O 2-α D α , 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.5 and 0<α<2; Li a Ni 1-b-c Mn b X c O 2-α D α , 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.5 and 0<α<2; Li a Ni b Co c L 1 d G e O2, 0.90≤a≤1.8, 0≤b≤0.9, 0≤c≤0.5, 0≤d≤0.5 and 0≤e≤0.1; Li a NiG b O2, 0.90≤a≤1.8 and 0.001≤b≤0.1; Li a CoG b O2, 0.90≤a≤1.8 and 0.001≤b≤0.1; Li a Mn 1-b G b O2, 0.90≤a≤1.8 and 0.001≤b≤0.1; Li a Mn2G b O4, 0.90≤a≤1.8 and 0.001≤b≤0.1; Li a Mn 1-g G g PO4, 0.90 ≤ a ≤ 1.8 and 0 ≤ g ≤ 0.5; Li (3-f) Fe2(PO4)3, 0≤f≤2; and Li a FePO4, 0.90≤a≤1.8.
